How Ingratiation Links to Counterproductive Work Behaviors: The Roles of Emotional Exhaustion and Power Distance Orientation - Yan, Miao; Xie, Yu-ping; Zhao, Jun; Zhang, Yong-jun; Bashir, Mohsin; Liu, Ying (Frontiers in Psychology, 2020)
We develop and test a model based on conservation of resources theory that links ingratiation to counterproductive work behaviors. The findings from a sample of 216 employees show that ingratiation has a positive effect on counterproductive work behaviors, and emotional exhaustion plays a mediating role in this relationship. Power distance orientation negatively moderates the relationship between ingratiation and emotional exhaustion and the indirect effect of emotional exhaustion on the relationship between ingratiation and counterproductive work behaviors. Specifically, the conditional indirect effect of ingratiation on counterproductive work behaviors through emotional exhaustion is more positive when power distance orientation is low than when it is high. The theoretical contributions and future research directions are discussed.